Low NIHSS score in large vessel occlusion stroke: optimal treatment and clinical controversies - Chen, Tonghe; Zhi, Wenhong; Hao, Ning; Li, Zaili; Cao, Xu; Chen, Qiuchi; Zhang, Li; Liu, Zhiguang (Frontiers in Neurology, 2025)
Acute ischemic stroke caused by large vessel occlusion (LVO) with low National Institutes of Health Stroke Scale (NIHSS) scores (≤5) presents a critical clinical dilemma regarding optimal management. While endovascular thrombectomy (EVT) is established for moderate-to-severe strokes, its role in milder cases remains controversial, balancing potential benefits against risks of intracranial hemorrhage and procedural complications. This review synthesizes evidence from observational studies, registry data, and meta-analyses comparing EVT with best medical therapy (including intravenous thrombolysis and antiplatelet treatment) in this population. Key findings indicate no significant difference in 90-day functional outcomes between EVT and medical management; across observational cohorts, EVT has been associated with higher symptomatic intracranial hemorrhage (sICH) and a possible increase in 90-day mortality, but these estimates derive from non-randomized data and may reflect selection bias and residual confounding. Subgroup analyses highlight the influence of occlusion location (proximal vs. distal), risk of early neurological deterioration (END), time window, and bridging therapy on treatment decisions: proximal occlusions (e.g., internal carotid artery, middle cerebral artery M1 segment) and high END risk may favor more aggressive intervention, while distal occlusions (e.g., M2 segment) often respond adequately to medical therapy with close monitoring. Clinical recommendations emphasize an individualized approach: prioritizing medical management for most patients, with EVT reserved for high-risk cases or those with neurological deterioration during observation. Future randomized controlled trials are needed to refine patient selection criteria and validate risk stratification tools for this challenging population.